Respective radiation output characteristics of transmission-target and reflection-target X-ray tubes with the same beam quality. (May 2019) - Wang, S.F.; Chiang, H.Y.; Liao, Y.J.; Liu, R.S.; Cheng, C.C.; Yang, H.W.; Wang, S.W.; Lin, Y.C.; Hsu, S.M.
Abstract: A transmission-target X-ray tube is different from a reflection-target X-ray tube based on how the radiation is generated; thus, the radiation output characteristics of these two tubes are different. This study explored the differences in radiation output of a transmission-target X-ray tube and a reflection-target X-ray tube when both tubes were in the same radiation beams. A Shimadzu transmission-target X-ray tube and a NanoRay Biotech reflection-target X-ray tube were used in the study. The measurement values from the ionization chamber were compared with Monte Carlo EGSnrc simulation results. At a depth of 5 cm within water, the percentage depth doses (PDDs) of the transmission-target X-ray tube and the reflection-target X-ray tube with the same beam qualities appeared to have the maximum differences of 3.0% and 5.0% for ionization chamber measurement values and Monte Carlo simulation values, respectively. For every PDD beyond a depth of 5 mm, the difference was within 2.0%, and both tubes agreed well with each other with respect to the PDD measurement results. When compared with the Monte Carlo simulation values, the dose profile measurement values of the ionization chamber for the transmission-target X-ray tube and the reflection-target X-ray tube appeared to have differences smaller than 2.0% within 90.0% dose ranges at every depth on the X-axis and Y-axis. The heel effect was observed on the Y-axis dose profile of the reflection-target X-ray tube. The PDD of the transmission-target X-ray tube reached the greatest level on the water surface and decreased with increasing within water depth. When applied in radiological therapy, the treatment dose could be effectively given to a superficial tumor; a lower dose would be received by peripheral normal tissues. Highlights: The transmission-target X-ray tube does not exhibit a heel effect. 43 and 80 kVp of the reflection and transmission tube have similar beam quality. The dose output of transmission is higher than reflection tube in same beam quality.